Improving color quality in goldfish (Carassius auratus) by giving of papaya seed flour (carica papaya) as a natural inhibitor in the gonad development process - Faulia, Neng Tian; Farastuti, Eko Rini (Universitas Djuanda, 2024)
Goldfish (Carassius auratus) is a freshwater ornamental fish growing fast and in demand in Indonesia. This study aimed to obtain the best dose for the treatment and determine the effect of papaya seed powder on gonadal infertility, thereby increasing the development of colour quality in Comet fish (Carassius auratus). This research was carried out from May to August 2023 which was carried out in the Aquatic Laboratory room of the Aquaculture Study Program, Faculty of Agriculture, Juanda University, Bogor, West Java Province. This study used comet fish weighing 14-17 g stocked with three fish/aquariums. The study used a completely randomized design with four treatments and three replications. Treatment P0 (without papaya seed flour), P1 treatment (5 g papaya seed flour), P2 treatment (10 g papaya seed flour), and P3 (15 g papaya seed flour). The parameters observed were colour, weight gain, body circumference, sperm volume and survival rate. The results showed significantly different (P<0.05) in colour, weight growth, body circumference, and sperm volume, with the best results in the P2 treatment with a colour scoring value of 24.93, weight growth of 15.78 grams, body circumference of 5.94 cm and a sperm volume of 0.06 ml. The range of water quality includes temperature 24 – 28.9 oC, pH 7 – 8.68, and DO 5 – 7.5 mg/L. The survival rate in adding papaya seed powder showed no significant difference (P>0.05) in survival results (SR) with a value of 100%.